Multiplayer Quiz Adventure Educational Game Arts and Culture Using the Fisher-Yates Shuffle Algorithm - Rahul Devnanza; Mursyidah Mursyidah; Atthariq Atthariq (Jurnal Teknologi Rekayasa Informasi dan Komputer, 2025)
The rapid development of games, with a wide variety of genres, includes strategy, adventure, arcade, puzzle, sports, and more, packaged in PlayStation games, PC games, and mobile devices. Games with educational content are better known as educational games. These educational games aim to stimulate interest in learning the subject matter while playing, so that with a sense of enjoyment, it is hoped that it will be easier to understand the material presented. As we know, arts and culture play a crucial role in shaping a nation's identity. Appreciating arts and culture has a positive impact in helping society understand the historical roots, values, and cultural heritage that form the basis of cultural diversity. However, often the teaching of arts and culture in educational environments does not create sufficient appeal and does not meet expected standards. Therefore, creative and innovative approaches are needed so that the younger generation can be more actively involved in learning and appreciating arts and culture in an interesting and interactive way. The author hopes that this video game will be an interesting alternative to traditional learning approaches. This game itself uses the Fisher-Yates Shuffle algorithm to randomize quiz questions so that each game has a different order. In this game, players are invited on an adventure to overcome the obstacles presented. Furthermore, players are expected to answer questions about arts and culture, which will broaden their knowledge and understanding. Furthermore, players will find these questions entertaining and challenging.